Factors Contributing to Corporate Farming Adoption Decision and Their Impact on Farmers’ Human Resources Performance - Lieli Suharti; Hani Sirine; Samuel Martono (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Corporate farming enhances agricultural efficiency and productivity, boosting sectoral competitiveness. Despite the Indonesian government’s efforts to establish corporate farming in multiple districts, the outcomes have fallen short of expectations. This study investigates factors influencing farmers’ decisions to adopt corporate farming and its effects on improving farmers' human resource (HR) performance. Key factors analyzed include support from farmer groups (Poktan), government, social networks, partnerships with the Business and Industrial World (DUDI), and initiator roles. Using data from 142 farmers in Temanggung and Wonosobo districts, collected through structured questionnaires and analyzed with SEM via SmartPLS 3.0, the study reveals that farmer decisions to adopt corporate farming are significantly influenced by Poktan support, government support, social support, and the initiator role. However, these decisions have no significant impact on HR performance. On the other hand, Poktan support, government support, and partnerships with DUDI directly enhance HR performance. To promote corporate farming, the study emphasizes the importance of strengthening Poktan, government, and social supports, alongside initiator roles. Furthermore, corporate farming activities require support from a highly skilled farmer workforce. The study also highlights the role of external factors, like DUDI partnerships, in improving HR performance. By integrating variables from the Technology Acceptance Model (TAM) into the agricultural sector, this study enriches the literature on corporate farming adoption and its impact on HR performance.